Impact of Founder on the IPO Flipping Activity during Pre and Post-Global Financial Crisis - Leow, Hon-Wei; Lau, Wee-Yeap (UI Scholars Hub, 2020)
This study examines the impact of the founder on the IPO flipping activity in the Malaysian stockmarket, especially the Main and ACE Market, across the Global Financial Crisis (GFC) periodfrom January 2006 to December 2016. Multiple regression models have been used to evaluate the interaction of the founder and other independent variables. Using three sub-periods, namely pre- GFC, GFC, and Post-GFC, our results show: Firstly, the founder by itself does not have any impact on flipping activity. However, the interaction of founder and oversubscription ratio reduces flipping activity in the pre-crisis period. Secondly, the interaction of founder and firm age is significant during the GFC period. Thirdly, in post-GFC, the interaction between founder-firm age, founder-offer period are essential factors. Overall, it is found that firm age and IPO offer period have an impact on flipping activity in the Main and ACE Market.